How to promote positive youth development in physical education? The experiences of a 5 physical educator and students through the delivery of Project SCORE! - Santos, Fernando (2018)
Confidence, character, competence and connection have been acknowledged as desired characteristics of positive youth development (PYD)-based programs titled the C's. Based on the 4 C's framework, an online tool called Project SCORE! has been designed to help coaches and parents, or other stakeholders facilitate PYD through a specific set of strategies, objectives and activities. However, research on PYD-focused teacher education programs, specifically using Project SCORE! is still scarce. The purpose of this case study was to analyze the influence of a PYD-focused intervention based on Project SCORE! on a physical education (PE) teacher's and his students' PYD behaviors. The participants were a PE teacher with extensive teaching and coaching experience and seven students involved in this participants' PE class. Data was collected through semi-structured interviews, nonparticipant observations, reflexive journaling and focus group interviews. Findings showed how the PE teacher was able to transition from an unintentional approach towards PYD to an intentional one which resulted in more PYD outcomes reported by his students after the PYD-focused intervention based on Project SCORE!. In addition, his coaching experience have him an unique outlook on how to develop a PYD mandate in PE. Future research should focus on implementing Project SCORE! in a broad array of contexts and understand how parents may be involved in this online platform.